Implikasi Manajemen Sarana dan Prasarana Terhadap Pembelajaran Bahasa Arab (Studi Kasus Lab. Bahasa Arab FAI-UMM) - Anisatu Thoyyibah; Mochammad Firdaus (Universitas Yudharta Pasuruan, 2021)
One of the elements to achieve educational goals is to produce quality human resources, including adequate educational infrastructure. In the language learning process, the environment becomes an important element that affects the learning process and students' motivation in improving language skills. The creation of the language environment can be realized through the provision of adequate learning infrastructure. The purpose of this study was to describe the implications of the management of facilities and infrastructure for learning Arabic related to student learning motivation at the Arabic Language Laboratory of FAI-UMM. This study uses a qualitative approach, with the data source in the form of a questionnaire distributed to students of the Faculty of Islamic Studies class 2018 who study Arabic intensively at the Arabic Language Laboratory, Islamic Studies Faculty, Muhammadiyah Malang University. The data collection techniques used the method of observation, questionnaires, and interviews. While the data analysis uses typology and triangulation. The results of this study indicate the implications of the management of facilities and infrastructure on student learning motivation at the Arabic Language Laboratory of FAI-UMM. This is evidenced by the percentage shown that not all students choose strongly agree (SS) in the points disseminated through a questionnaire.